Pour DF.DC :
[tex]\overrightarrow{DF}(\frac{DC}{2} , EF) \rightarrow \overrightarrow{DF}(2 , 3)\\\overrightarrow{DC}(DC, 0) \rightarrow \overrightarrow{DC}(4 , 0)\\\\\overrightarrow{DF}.\overrightarrow{DC} = x_{\overrightarrow{DF}}*x_{\overrightarrow{DC}}+y_{\overrightarrow{DF}}*y_{\overrightarrow{DC}}=2*4+3*0\\\overrightarrow{DF}.\overrightarrow{DC} = 8[/tex]
Pour DA.CB :
[tex]\overrightarrow{DA}(0 , DA) \rightarrow \overrightarrow{DA}(0, 4)\\\overrightarrow{CB}(0,CB) \rightarrow \overrightarrow{CB}(0, 4)\\\\\overrightarrow{DA}.\overrightarrow{CB} = x_{\overrightarrow{DA}}*x_{\overrightarrow{CB}}+y_{\overrightarrow{DA}}*y_{\overrightarrow{CB}}=0*0+4*4\\\overrightarrow{DA}.\overrightarrow{CB} = 16[/tex]
Pour FD.FC :
[tex]\overrightarrow{FD}(-\frac{DC}{2} , -EF) \rightarrow \overrightarrow{FD}(-2, -3)\\\overrightarrow{FC}(\frac{DC}{2},-EF) \rightarrow \overrightarrow{FC}(2, -3)\\\\\overrightarrow{FD}.\overrightarrow{FC} = x_{\overrightarrow{FD}}*x_{\overrightarrow{FC}}+y_{\overrightarrow{FD}}*y_{\overrightarrow{FC}}=(2*-2)+(-3*-3)\\\overrightarrow{FD}.\overrightarrow{FC} = 5[/tex]
Pour DF.DB :
[tex]\overrightarrow{DF}(\frac{DC}{2} , EF) \rightarrow \overrightarrow{DF}(2, 3)\\\overrightarrow{DB}(DC,-CB) \rightarrow \overrightarrow{DB}(4, -4)\\\\\overrightarrow{DF}.\overrightarrow{DB} = x_{\overrightarrow{DF}}*x_{\overrightarrow{DB}}+y_{\overrightarrow{DF}}*y_{\overrightarrow{DB}}=(2*4)+(3*-4)\\\overrightarrow{DF}.\overrightarrow{DB} = -4[/tex]